Relationships between the spatial distribution of oligochaetes (Annelida, Clitellata) and environmental variables in a temperate estuary system of South America (Río de la Plata, Argentina) - Armendáriz, Laura Cecilia (2011)
The oligochaete assemblage on the Argentine coast of the Río de la Plata estuary was sampled seasonally within environments having different types of disturbances. Three habitats were sampled: sediments free of vegetation, sediments within bullrush stands and substrates with Limnoperna fortunei. The species richness, evenness and Shannon-Wiener diversity values were different among those habitats. The only dominant species (according to the Kownacki index) was Nais variabilis. Mean density values varied between 400 and 199,500 ind·/m2. Organic matter, ammonium and phosphates correlated positively with the mean oligochaete abundance, but not with the granulometry. Physicochemical variables and nutrient levels were measured and their relation to the sampling sites assessed through a principal component analysis (41.8% cumulative variance). The canonical correspondence analysis (41.2% cumulative variance) indicated that the oligochaetes distributed along both a eutrophication-pollution gradient and a turbidity-conductivity gradient. These results would be useful for assessing the ecological status of estuaries for a subsequent implementation of appropriate sustainability-management policies.